2013
DOI: 10.21914/anziamj.v54i0.6284
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solutions for thin film flow down the outside and inside of a vertical cylinder

Abstract: We consider a model for thin film flow down the outside and inside of a vertical cylinder. Our focus is the effect the curvature of the cylinder has on the gravity driven instability of the advancing contact line and to simulate the resulting fingering patterns that form due to this instability. The governing partial differential equation is fourth order with a nonlinear degenerate diffusion term that represents the stabilising effect of surface tension. We present numerical solutions obtained by implementing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…While ADI methods have been popular in solving thin-film-type equations like ours [18,24,29], more recent work has shown that parallelized multigrid methods may offer the greatest potential for efficiency [55,56]. However, we find that an ADI approach is sufficiently fast for the scale of the presented simulations.…”
Section: Alternating Direction Implicit Schemementioning
confidence: 81%
See 4 more Smart Citations
“…While ADI methods have been popular in solving thin-film-type equations like ours [18,24,29], more recent work has shown that parallelized multigrid methods may offer the greatest potential for efficiency [55,56]. However, we find that an ADI approach is sufficiently fast for the scale of the presented simulations.…”
Section: Alternating Direction Implicit Schemementioning
confidence: 81%
“…The coalescence and separation simulations depicted in figures 3-5 have been presented for comparison with real observations like those in figure 1. Similar droplet behaviours have been studied before [16,18,19,24,29,32,34], but have rarely been studied in the context of spray droplets on leaves.…”
Section: Coalescing and Separating Dropsmentioning
confidence: 86%
See 3 more Smart Citations